Optimasi pH Dan Salinitas Media Kultur Terhadap Pertumbuhan Dan Aktivitas Protease Ektraseluler Bakteri Bacillus Firmus Dari Ekosistem Padang Lamun Nusa Lembongan – Bali. - Muhammad Zainuddin; Delianis Pringgenies; Ocky Karna Radjasa; Haeruddin Haeruddin; Aninditia Sabdaningsih; Vivi Endar Herawati (Journal of Tropical Marine Science, 2022)
Sponges are sponges that live on the bottom of the water. Sponges have a symbiotic relationship with bacteria. Chalinula pseudomolitba is a type of sponge that lives in the waters of Nusa Lembongan Bali and has the symbiotic bacterium Bacillus firmus. Bacillus firmus has proteolytic activity by producing extracellular protease enzymes. These bacteria have the potential to be developed into probiotics in remediating protein in organic waste left over from shrimp pond feed. In an effort to produce Bacillus firmus bacteria for probiotics, it is necessary to optimize the pH and salinity of the culture media. The purpose of this study was to optimize the pH and salinity of Bacillus firmus bacterial culture media from the symbiont sponge Chalinula pseudomolitba which has proteolytic activity. The research used aboratory experimental method. Research has succeeded in conducting tests to optimize pH and salinity of culture media on the growth and activity of extracellular protease enzymes in bacteria. The results showed that Bacillus firmus had the best growth rate and protease activity under culture conditions with a pH of 8 with values of 0,174 and 31,763 IU/ml, respectively. In addition, it also has the best growth rate and protease activity at media salinity of 30 ppt with values of 0,186 and 35,278 IU/ml.